1996
DOI: 10.1021/ac950240a
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Oxidoreductase-like Activity of Intact Bacterial Cells by an Amperometric Method Using a Membrane-Coated Electrode

Abstract: The oxidation of D-glucose and nicotinic acid by intact cells of Gluconobacter industrious and Pseudomonas fluorescens, respectively, is successfully measured by an amperometric method using such compounds as Fe(CN)6(3-), p-benzoquinone, and dichlorophenolindophenol as electron acceptors. Analysis of the experimental results reveals that the intact cells behave like oxidoreductases whose kinetics follows a Michaelis-Mententype equation. The catalytic behavior is explained by a model which treats the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 22 publications
1
68
0
Order By: Relevance
“…The work [14] describes an amperometric biosensor for ethanol detection, which is modified by HCF and contains the bacterium G. oxydans CCM 1783 (ATCC 621). DCPIP and BQ were used in combination with the suspension of G. industrius (IFO 3260) for current generation at electrocatalytic glucose oxidation [15]. We have found no literature data on assessment of the efficiency of mediators at their application in combination with the same strain.…”
Section: Hydrophilic Mediatorsmentioning
confidence: 99%
“…The work [14] describes an amperometric biosensor for ethanol detection, which is modified by HCF and contains the bacterium G. oxydans CCM 1783 (ATCC 621). DCPIP and BQ were used in combination with the suspension of G. industrius (IFO 3260) for current generation at electrocatalytic glucose oxidation [15]. We have found no literature data on assessment of the efficiency of mediators at their application in combination with the same strain.…”
Section: Hydrophilic Mediatorsmentioning
confidence: 99%
“…The rate of electrocatalytic glucose oxidation by bacterial cells was assessed by analyzing the dependences I -t [16]. The current is proportional to reaction rate:…”
Section: Assessment Of Mediator Efficiencymentioning
confidence: 99%
“…The work of T. Ikeda et al [16] is apparently fundamental in this respect. The authors have shown that the catalytic activity of the system "mediator -bacterial cell" can be characterized by three quantities: the maximum reaction rate and the ratios of the Michaelis constant to the distribution constant for the substrate (K S /K S,p ) and to that for the electron acceptor (K M /K M,p ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To achieve the continuous electron transfer (i.e., electron leak) from microbial cells with minimum amounts of external artificial electron acceptors (or to reduce the amounts and cost of external artificial electron acceptors), the re-oxidation reaction of the reduced form of the artificial electron acceptors would be required. When an electrode was used as a final electron acceptor, the artificial electron acceptor works as a mediator to shuttle electrons from the microbe to the electrode (Ikeda et al, 1996;Kim and Kim, 1988). The electrochemical metabolic regulation of P. freudenreichii has also been studied using hexacyanoferrate (III) as an artificial mediator (Emde and Schink, 1990).…”
Section: Introductionmentioning
confidence: 99%